Human Papillomavirus Positivity and Frequency of Genotypes in Servical Samples of Women Living in Sivas Region - Yıldırım, Dilara; Yıldırım, Malik Ejder; Bakıcı, Mustafa Zahir (Fırat University, 2013)
Objective: Our aim in this study, is to determine the frequency of human papilloma virus DNA and its genotypes, and to evaluate the association between servical smear and results. Materials and Methods: Our study was realised with 140 women who is between 21 and 67 years. HPV DNA was researched with PCR method in servical smears of patients and HPV genotyping was carried out with reverse hybridization procedure in HybriMax (Hybribio). Then, smears taken with servical brush were spreaded on slides and they were sent to pathology department for examining. Results: In our study, % 6,4 of case have HPV positiveness. In our study, the most frequent genotype of HPV is HPV type 6 (%25). The second is HPV 16 (%16,6). The ratio for pathologic negativity and HPV positiveness is %77,8. It were detected that %94,7 of the patients with smear negative are HPV negative and %5,3 of them are HPV positive. %33,3 of the patients with condylomata accuminata are HPV negative, %66,7 of them are HPV positive. Patient diagnosed as VIN is only one and detected HPV negativity. Conclusion: The degree of HPV DNA positivity which we detected in our region is high. In addition to cytologic evaluation, molecular techniques are also important for following the disease. Molecular works will be useful to determine the priority of genotypes that will be use for routine vaccination in our country, in future.

Amaç: Bu çalışmada amacımız, yöremizdeki HPV DNA genotiplerinin sıklığını belirlemek, servikal sürüntü ile sonuçlar arasındaki ilişkiyi değerlendirmektir. Gereç ve Yöntem: Çalışmamız, yaşları 21 ile 67 arasında değişmekte olan 140 kadın olgu üzerinde yapıldı. Hastalardan alınan servikal örneklerde PCR yöntemi ile HPV DNA araştırıldı ve Otomatize HybriMax cihazında revers hibridizasyon yöntemi ile HPV genotiplendirilmesi yapıldı. Ayrıca servikal fırça ile alınan smearlar lam üzerine yayıldı ve incelenmek üzere hastanemiz patoloji laboratuvarına gönderildi. Bulgular: Çalışmamızda, olguların % 6,4'ünde HPV DNA pozitifliğine rastlandı. HPV genotip 6, % 25 oranında en sık bulunurken ikinci sıklıkta genotip 16, % 16,6 oranında rastlanmıştır. Bu hastaların patoloji negatifliği ve HPV pozitifliği % 77,8 oranındadır. Smear sonuçlarına göre smear negatif olan hastaların %94,7'sinde HPV negatif, %5,3'ünde pozitif bulunmuştur. Kondiloma aküuminatalı hastaların %33,3'ünde HPV negatif, %66,7'sinde HPV pozitiftir. Vajinal intraepitelyal neoplazi (VIN) tanısı konan hasta bir tane olup, HPV negatif olarak tespit edilmiştir. Sonuç: Yöremizde tespit ettiğimiz HPV DNA pozitifliği yüksek bir orandadır. Sitolojik takibin yanında moleküler testler de takipte oldukça önemlidir. Moleküler çalışmalar, gelecekte ülkemizde rutin aşılama çalışmalarında kullanılacak genotiplerin önceliğini belirlemede yararlı olacaktır.
Sivas Bölgesinde Yaşayan Kadınlarda Servikal Örneklerde Human Papillomavirüs Pozitifliği ve Genotiplerinin Sıklığı